Semiconductor quantum dots: a versatile platform for photoredox organic transformation. Issue 7 (30th January 2023) - Wu, Hui-Li; Qi, Ming-Yu; Tang, Zi-Rong; Xu, Yi-Jun
Abstract : A summary of the research progress of diverse organic transformations over semiconductor quantum dot based photofunctional catalysts is provided. Abstract : Semiconductor quantum dots (QDs), as a newfashioned light-absorbing material with great promise in artificial photosystems, generally exhibit attractive photoactivity and selectivity in organic photoredox transformation thanks to their tunable redox potential, high-efficiency light harvesting capability, and high extinction coefficient in the visible region. Utilizing QDs as a versatile platform to convert organic compounds into value-added feedstocks provides an effective way to alleviate energy and chemical feedstock supply problems. In this review, we concisely summarize the basic principles of photocatalytic organic conversions over semiconductor QDs and the effects of grain size, surface active sites and ligands on their catalytic performance. Then, we highlight the recent progress of QDs enabling multifarious photocatalytic organic transformations, including nitroaromatic reduction, selective alcohol oxidation, sulfide oxidation, C–H functionalization and so on. In the end, we discuss the current challenges and future prospects in further developing efficient semiconductor QD-based photocatalysts toward photoredox-catalyzed organic conversion.